2011
DOI: 10.1007/s10695-011-9508-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo protective effect of dietary curcumin in fish Anabas testudineus (Bloch)

Abstract: The present study describes, for the first time, the protective effect of natural curcumin in vivo in a lower vertebrate, a teleost, Anabas testudineus (Bloch). Two doses of curcumin 0.5 and 1% were supplemented in the 40% protein feed and fed to fish for the periods, 2 and 8 weeks. The antioxidant status, protein content, and the tissue structure in experimental fish were examined after the short-term and long-term feeding. In all the curcumin fed groups, the lipid peroxidation product, thiobarbituric acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 38 publications
4
35
1
3
Order By: Relevance
“…In the present study, fish fed the high dose of curcumin (20 g/kg diet) exhibited degeneration vacuoles in hepatocytes and large accumulation of hemosiderin around blood vessels (T6, 1f). That disagrees with the study by Manju (2012) who, reported that in the curcumin-treated Anabas sp., there were no histological changes in the liver after feeding two doses of curcumin at 5 and 10 g/kg.…”
Section: Discussioncontrasting
confidence: 93%
“…In the present study, fish fed the high dose of curcumin (20 g/kg diet) exhibited degeneration vacuoles in hepatocytes and large accumulation of hemosiderin around blood vessels (T6, 1f). That disagrees with the study by Manju (2012) who, reported that in the curcumin-treated Anabas sp., there were no histological changes in the liver after feeding two doses of curcumin at 5 and 10 g/kg.…”
Section: Discussioncontrasting
confidence: 93%
“…Similar results have been obtained in other fish such as Jian carp (Cyprinus carpio var. Jian) and Nile tilapia (Oreochromis niloticus), in which treatment with curcumin reduced the proinflammatory cytokine expression levels to normal (Cao et al 2015;Mahfouz 2015) and had positive effects in cultured fish (Manju et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of CUR has so far been found to be excellent (Clarke & Mullin ; He et al . ), and the compound has shown positive effects on growth of fish in aquaculture (Manju, Akbarsha & Oommen ; Manju et al . ; Mahfouz ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How do the curcumins contained in turmeric improve liver function and increase egg diameter? Turmeric and curcumin have been used as hepatoprotectors to prevent and cure liver damage (Manju, Akbarsha & Oommen, ). Turmeric has traditionally been used in Ayurveda and folk medicine to treat ailments, and modern science has provided the basis for its use in the treatment of liver disorders (Gupta et al., ).…”
Section: Discussionmentioning
confidence: 99%